2023
DOI: 10.1136/bmjopen-2022-068545
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic prescription for children with acute respiratory tract infections in rural primary healthcare in Guangdong province, China: a cross-sectional study

Diqiong He,
Feifeng Li,
Jiong Wang
et al.

Abstract: ObjectivesThe objective of this study is to understand the characteristics and patterns of the first antibiotic prescriptions for children with acute respiratory infections (ARIs) in rural primary healthcare (PHC) in Guangdong province, China.DesignCross-sectional study.Setting and participantsWe used prescription data generated from the electronic medical record system of 37 township hospitals in two counties of Shaoguan City, Guangdong province. 46 699 first prescriptions for ARIs in children aged 0–18 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
1
0
0
Order By: Relevance
“…Recent retrospective cross-sectional studies focusing on pediatric antibiotic use for upper respiratory infections have revealed higher prescribing rates and a greater proportion of injection formulations in underdeveloped regions [15]. Similar conclusions were drawn in studies concerning rural primary care settings in Guangdong province [16]. Moreover, children in less developed provinces face heightened risks of antibiotic misuse, both at home and during medical consultations.…”
Section: Introductionsupporting
confidence: 56%
“…Recent retrospective cross-sectional studies focusing on pediatric antibiotic use for upper respiratory infections have revealed higher prescribing rates and a greater proportion of injection formulations in underdeveloped regions [15]. Similar conclusions were drawn in studies concerning rural primary care settings in Guangdong province [16]. Moreover, children in less developed provinces face heightened risks of antibiotic misuse, both at home and during medical consultations.…”
Section: Introductionsupporting
confidence: 56%